2012
DOI: 10.3329/bjar.v37i2.11234
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Diffusion of Power Tillers in Bangladesh

Abstract: The present study examines the extent of adoption of power tillers (PT) in  Bangladesh and analyzes the variation in adoption across regions and across farms in selected areas to investigate the justification for wider use of power tillers. Primary and secondary data were used. Primary data were collected from 267 sample farmers from eight villages of four upazilas of four districts using proportionately stratified random sampling technique. Secondary data were collected from different published sources. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 1 publication
4
11
0
Order By: Relevance
“…Moreover, these older farmers may be more "set in their ways", interested in following traditional methods familiar to them rather than adopting modern farming techniques. The similar outcome have found and explained in the articles written by Acquah and Quayum et al [39,40].…”
Section: Econometric Estimation Of Factors Affecting the Farmers' Adasupporting
confidence: 72%
See 2 more Smart Citations
“…Moreover, these older farmers may be more "set in their ways", interested in following traditional methods familiar to them rather than adopting modern farming techniques. The similar outcome have found and explained in the articles written by Acquah and Quayum et al [39,40].…”
Section: Econometric Estimation Of Factors Affecting the Farmers' Adasupporting
confidence: 72%
“…These areas provide rife opportunity for further empirical study to provide evidence as to which, if any, is connected with the observation of a negative sign of the coefficient and its statistical significance. Other studies, such as that of Quayum and Ali (2012) [40] have shown that family size was negatively and significantly related to adoption of technologies, but there is no definitive causation shown in the literature reviewed for preparing this work.…”
Section: Econometric Estimation Of Factors Affecting the Farmers' Adamentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, these older farmers may be more interested in the following traditional methods familiar to them rather than adopting modern farming techniques. Acquah (2011) and Quayum et al (2012) found similar results but negative significance. Their findings may be because young adults have more motivation to act on perceived changes in order to cope with it.…”
Section: Correlation Estimation Of Some Factors Influencing the Farmesupporting
confidence: 66%
“…This tillage implement is introduced basically for land preparation, but now it is used for different purposes depending on environment, ability of farmers for buying attachments, and availability of credit facilities. The percentage of area cultivated under PT is 67% and the average growth rate of power tillers in Bangladesh was 21% during 1993-2003(Quayum and Ali, 2012. There are about 7,00,000 PTs in Bangladesh (Hossain, 2014).…”
Section: Introductionmentioning
confidence: 99%